The electrodissolution and passivation of mild steel in alkaline sulphide solutions - Salvarezza, Roberto Carlos (1981)
The electrodissolution and passivation of mild steel in alkaline sulphide solutions at 25°C is investigated by the use of steady state and transient electrochemical techniques and by scanning electron microscopy and energy dispersive X-ray analysis. The electrodissolution and passivation processes are explained by the initial competitive adsorption of OH−, HS− and H2O and the subsequent charge transfer and proton transfer processes involving the OH and HS adsorbed species. The former is responsible for the passivation of the metal by an oxide metal layer while the second species undergoes two different reactions yielding in one case a precipitated mackinawite film on the metal, which is a poorly protective layer, and in the other a soluble Fe(II) species which can be detected by chemical analysis. The contribution of the reactions starting from each adsorbed species depends on the HS−/OH− concentration ratio in the solution. The initiation of pitting on iron is also explained through the postulated reaction pattern.